Microbial communities along biogeochemical gradients in a hydrocarbon‐contaminated aquifer. (1st July 2013) - Tischer, Karolin; Kleinsteuber, Sabine; Schleinitz, Kathleen M.; Fetzer, Ingo; Spott, Oliver; Stange, Florian; Lohse, Ute; Franz, Janett; Neumann, Franziska; Gerling, Sarah; Schmidt, Christian; Hasselwander, Eyk; et al.
Summary: Micro‐organisms are known to degrade a wide range of toxic substances. How the environment shapes microbial communities in polluted ecosystems and thus influences degradation capabilities is not yet fully understood. In this study, we investigated microbial communities in a highly complex environment: the capillary fringe and subjacent sediments in a hydrocarbon‐contaminated aquifer. Sixty sediment sections were analysed using terminal restriction fragment length polymorphism (T‐RFLP) fingerprinting, cloning and sequencing of bacterial and archaeal 16S rRNA genes, complemented by chemical analyses of petroleum hydrocarbons, methane, oxygen and alternative terminal electron acceptors. Multivariate statistics revealed concentrations of contaminants and the position of the water table as significant factors shaping the microbial community composition. Micro‐organisms with highest T‐RFLP abundances were related to sulphate reducers belonging to the genus Desulfosporosinus, fermenting bacteria of the genera Sedimentibacter and Smithella, and aerobic hydrocarbon degraders of the genus Acidovorax . Furthermore, the acetoclastic methanogens Methanosaeta, and hydrogenotrophic methanogens Methanocella and Methanoregula were detected. Whereas sulphate and sulphate reducers prevail at the contamination source, the detection of methane, fermenting bacteria and methanogenic archaea further downstream points towards syntrophic hydrocarbon degradation.